2018
DOI: 10.1007/s10722-018-0726-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic characterization of barley (Hordeum vulgare L.) landraces in the Canary Islands

Abstract: Barley has been continuously cultivated in the Canary archipelago for millennia, and to this day landrace barley is the preferred choice for cultivation. We have morphologically and genetically characterized 57 landraces collected during the twentyfirst century and conserved in genebanks. The majority of accessions were of the six-row type. Although landraces from the same island tended to be similar, the results showed morphological and genetic diversity both within and in the case of genetic data among islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Islands are natural laboratories for the study of the evolution and ecology of wild plants and endemisms [2][3][4]. Therefore, due to their isolation and special environmental features, islands are also considered as sites of special interest to prospect and conserve plant genetic resources [5,6]. The Greek archipelago includes ca.…”
Section: Introductionmentioning
confidence: 99%
“…Islands are natural laboratories for the study of the evolution and ecology of wild plants and endemisms [2][3][4]. Therefore, due to their isolation and special environmental features, islands are also considered as sites of special interest to prospect and conserve plant genetic resources [5,6]. The Greek archipelago includes ca.…”
Section: Introductionmentioning
confidence: 99%
“…Forty five barley samples were analyzed, 42 were ancient landraces from the Canary Islands, and three were commercial ones used as control. Data about island of origin, spike density, number of rows, aleurone layer color, and length of vegetative cycle are shown in Table 1 (Hagenblad et al., 2019). Most of the barley samples were of six rows, and only four (two landraces and two commercial samples barley) were of two rows.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular studies carried out using single nucleotide polymorphism concluded that their genetics have remained intact for the last 900 years (Leino, Hagenblad, Edqvist, & Strese, 2009), which gives an idea of the invaluable legacy that these landraces provide. However, the production of this cereal in the Canary archipelago has markedly decreased in the first two decades of the 21st century, which put these ancient landraces at serious risk, not only for the loss of this genetic heritage but also because of the disappearance of the landscapes associated with this crop (Hagenblad et al., 2019). Knowledge of the nutritional profile of traditional barley landraces of the Canary Islands is a good way to increase the value of this genetic heritage, and thereby encouraging its use and promotion.…”
Section: Introductionmentioning
confidence: 99%
“…1 Map of the studied area. Geography of the Canary Islands and location of the Canary archipelago (inset) Hagenblad et al 2019). The period when this isolation arose on the archipelago is not known.…”
Section: Barley Cultivation In Hispanic Timesmentioning
confidence: 99%